ZONASI TINGKAT KERENTANAN TERHADAP BENCANA BANJIR DI KECAMATAN GUNUNG PUTRI KABUPATEN BOGOR - Astri Rusbianti Utami; Hanny Wahidin Wiranegara; Herika Muhamad Taki (Universitas Trisakti, 2021)
Flood is a phenomenon of submerging or inundating of an area. Based on the Bogor Regency Regional Regulation No. 4 of 2019 concerning the 2018-2023 Regional Medium-Term Development Plan, there are seven sub-districts in Bogor Regency that have a high level of vulnerability to flood disasters. One of these sub-districts is Gunung Putri District. This sub-district is the worst and most affected by the flood disaster due to the overflow of the Cikeas River and the Cileungsi River that surrounds it during high rainfall intensity for a long time. The purpose of this research is to arrange zoning based on the level of vulnerability to flood disasters. The method used is overlay and scoring techniques. The level of vulnerability is determined based on the river buffer, elevation, slope, and land use. The results showed a zoning map of the level of flood vulnerability in Gunung Putri District. The zone with a high level of flood vulnerability is 3864.83 Ha, the moderate zone is 1662.87 Ha, and the low is 561.68 Ha from the area of Gunung Putri District.